Molecular detection of canine viral infectious diseases in China: an investigation from 2018 to 2024 - Liu, Caihong; Chen, Yalei; Cui, Ningning; Yang, Yihang; Ding, Hangtian; Wu, Hongchao; Liu, Yuxiu; Tian, Kegong; Xu, Xingang (Frontiers in Veterinary Science, 2026)
To analyze the prevalence of canine viral diseases in China, including canine parvovirus type 2 (CPV-2), canine coronavirus (CCoV), canine distemper virus (CDV), canine herpesvirus type 1 (CHV-1), canine parainfluenza virus (CPIV), canine influenza virus (CIV), canine respiratory coronavirus (CRCoV), canine adenovirus 2 (CAV-2), canine adenovirus 1 (CAV-1), and canine rotavirus (CRV), a total of 2,492 samples from dogs in 22 provinces were tested between 2018 and 2024. The results showed that 1,236 dogs (49.6%) tested positive for one or more pathogens, CPV-2 (30.6%) being the most commonly detected, with CPV-2c being the most common genotype. The prevalence of CPV-2, CCoV, CDV, and CHV-1 varied significantly depending on the season, geographical location, and age, with young dogs (<6 months) being more susceptible to infection. The positive rates of CPV-2 and CDV were significantly higher in unvaccinated dogs than in vaccinated ones, whereas infections with CCoV, CPIV, CAV-2, and CAV-1 were not strongly associated with vaccination status. In the serological survey, the protective rates of 398 vaccinated dogs to CPV-2, CDV, CAV-1, CAV-2 and CPIV were 76.9, 72.1, 84.4, 85.7 and 49.0%, respectively. The emergence of a distinct phylogenetic clade of the CPIV F gene may contribute to the reduced protective efficacy against CPIV. Overall, these findings reveal the complex epidemiology of ten canine viral pathogens in China, highlighting the critical need for targeted prevention strategies and more effective vaccine development.